Determination of Rheological Properties and Dispersion Quality of Shear Thickening Fluid - Yanen, Cenk; Solmaz, Murat Yavuz; Aydoğmuş, Ercan (Osman SAĞDIÇ, 2021)
In this research, the rheological properties of non-Newtonian shear thickening fluid (STF) composed of nano-sized solid particles have been investigated. The best conditions have been determined by optimizing both the experimental production method and the rheological measurement system of STFs. Mechanical, ultrasonic, and both mechanical and ultrasonic mixing methods were used in the production of STFs that nano-sized silica particle (solid: aerosil) and polyethylene glycol (liquid medium: PEG). Also, the spacing between the plates was changed during the rheological measurements and the effect on the rheological character of the suspension was also compared. Although the best homogenization was obtained with the ultrasonic mixer in the produced STFs, the lowest performance was observed in the rheological measurements of these samples. In STFs obtained at high mixing speed with a mechanical mixer, the viscosity of the fluid increased abruptly with increasing shear rate. In the measurements, it was observed that the gap change between the parallel plates did not affect the rheological characteristics much.

Kayma altında katılaşan sıvılar (KAKS), sıvı ortamda dağıtılmış nano boyutlu katı partiküllerden oluşan Newtonyan olmayan özel bir akışkan çeşididir. KAKS’ların viskozitesinde artan kayma hızı ile birlikte ani bir artış görülür, sahip oldukları bu özellik tersinirdir ve viskoziteyi artıran gerilim ortadan kalktığında viskoziteleri ilk hallerine geri döner. KAKS’ların üretimi için katı ortam olarak kullanılan silika partiküller polietilen içerisinde üç farklı yöntem kullanılarak dağıtılmış ve üretim yönteminin dispersiyon kalitesine ve reolojik özelliklere olan etkisi incelenmiştir. Reolojik ölçümler sırasında plakalar arasındaki boşluk da değiştirilmiş ve süspansiyonun reolojik karakterine olan etkisi gözlenmiştir. Yapılan incelemelerde dispersiyon kalitesi en yüksek numunelerin ultrasonik karıştırıcı kullanılarak yapılanlar olduğu ancak reolojik özellikleri negatif etkilediği tespit edilmiştir. Reolojik ölçümlerde paralel plakalar arasındaki boşluk değişiminin grafik karakteristiğine etki etmediği gözlenmiştir.
Kayma Altında Katılaşan Sıvıların Reolojik Özelliklerinin ve Dispersiyon Kalitesinin Belirlenmesi
Keywords: Engineering; Mühendislik